2004
DOI: 10.1590/s1806-83242004000100016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health on quality of life among the elderly population of Joaçaba, Santa Catarina, Brazil

Abstract: The objective of this study was to investigate the impact of oral health conditions on the quality of life of elderly people in Joaçaba - SC, in Southern Brazil. A survey based on systematic sampling of clusters was carried out with 183 elderly people that belong to old age groups. The survey was conducted in order to assess the oral conditions of the participants (use of and need for prosthesis) based on the criteria from the World Health Organization publication "Oral Health Surveys, Basic Methods", 4th edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
3
17

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 8 publications
3
14
3
17
Order By: Relevance
“…No estudo de Biazevic et al 5 , os autores observaram que não havia impacto na saúde bucal relacionado ao uso de prótese total, mas existia essa interferência associada à necessidade de prótese total superior e inferior. Nunes & Abegg 27 encontraram em sua investigação que a dor de dente e a necessidade de próteses dentárias foram os principais fatores que afetaram a autopercepção da saúde bucal de idosos do sul do Brasil.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No estudo de Biazevic et al 5 , os autores observaram que não havia impacto na saúde bucal relacionado ao uso de prótese total, mas existia essa interferência associada à necessidade de prótese total superior e inferior. Nunes & Abegg 27 encontraram em sua investigação que a dor de dente e a necessidade de próteses dentárias foram os principais fatores que afetaram a autopercepção da saúde bucal de idosos do sul do Brasil.…”
Section: Discussionunclassified
“…Medidas de autopercepção dizem mais como está sendo afetada a rotina diária do indivíduo e da população em geral do que as realizadas com base em um ambiente clínico 5 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Biazevic et al (2004) 6 studied elderly people in a city in southern Brazil and emphasized the importance of maintaining the natural teeth and of carrying out oral rehabilitation by means of prosthetic treatment for quality of life relating to oral health. Nunes & Abegg (2008) 22 concluded that elderly individuals who were in need of total dentures attributed a higher negative impact on their self-perceived oral heath, particularly regarding their chewing function.…”
Section: Discussionmentioning
confidence: 99%
“…13 Among the factors that can infl uence the perception of oral health are socioeconomic characteristics, 4,12,17,27 such as educational level and income, and clinical conditions, 4,6,25,27 such as dental loss and the use and need for dentures. Despite the importance of assessing self-perception of oral health, few studies carried out in Brazil have focused on this topic using representative samples.…”
Section: Introductionmentioning
confidence: 99%